Substrate, temperature, and magnetic field dependence of electric polarization in mixed-stacking tetralayer graphenes - Patrick Johansen Sarsfield; Aitor Garcia-Ruiz (艾飛宇); Vladimir I. Fal'ko (Physical Review Research)
Polytypes of tetralayer graphene (TLG: Bernal, rhombohedral, and mixed stacking) are crystalline structures with different symmetries. Among those, mixed-stacking tetralayers lack inversion symmetry, which allows for intrinsic spontaneous out-of-plane electrical polarization, inverted in the mirror-image pair, ABCB and ABAC stackings. Here, we compare the intrinsic polarization of such TLGs with the symmetry-breaking effect of a substrate, which can also generate out-of-plane electric dipole moments with different sizes in all four polytypes, including ABCB and ABAC twins. We analyze their temperature and magnetic field dependence, in view of understanding the origin of the recently measured Kelvin probe force microscopy maps of tetralayer flakes [S. S. Atri et al.Adv. Phys. Res. 3, 2300095 (2023)10.1002/apxr.202300095], and notice that the intrinsic contribution could be singled out based on magnetic field dependence of polarization measured at low temperatures.